Quality improvement: A practical nursing program's admission test. (February 2019) - Jeffrey, Paul; Harris, Robin; Sherman, Jan
Abstract: Introduction: Academic institutions are under pressure to maintain a nearly flawless retention rate, while graduating successful students. The use of standardized admission tests to provide data driven decisions regarding applicant selection is common. The varying reliability and validity of current standardized tests inspired a large Canadian academic institution to use a faculty developed admission test for admission to its practical nursing (PN) program. Methods: The target population for this project was a purposive, convenience sample of graduated PN students from a large publically funded polytechnic institution in southern Ontario, Canada, who had completed the Canadian Practical Nurse Registration Examination (CPNRE) within 2014–2016 ( n = 293). Data was obtained retrospectively, and included program entry grade-point average (GPA) and CPNRE result, as well as chemistry, English, biology, and math admission test scores. Results: The predictors of chemistry, English, math admission test scores, and program entry GPA did not have an effect beyond the effects of the model's predictors. In this model, the R 2 suggests that 9% of the variance can be explained, and 91% not explained. In consideration of all independent variables, findings indicate that mean biology admission test scores ( M =74.96) are a predictor of student CPNRE success. Additionally, students who pass the CPNRE have a higher program GPA. Conclusions: Academic factors including program entry GPA, English, math, biology and chemistry admission scores are a fragment of the characteristics to be considered when determining the predictability of success in PN students. Therefore, it is imperative that program admission processes identify and measure nonacademic program entry criteria, as academic criterion have limited predictability. Furthermore, in isolation, academic admission criteria could be used to identify at-risk-students for appropriate remediation/counselling or as a placement test.